Perancangan Regulasi Tegangan AC - DC Menggunakan Filter Pasif - Agus Prasetyo; Fajar Bima D.R; Hendi Matalata (Journal of Electrical Power Control and Automation (JEPCA), 2020)
The adapter / power supply is a DC voltage source that is used to provide voltage or power to various electronic circuits that require DC voltage to operate. The main circuit of the power supply is  a rectifier, which is a circuit that converts an alternating signal (AC) into a direct signal (DC). The conversion process starts from rectification by the diode. In this paper, the Ripple Voltage Filter is carried out using a passive filter and the average voltage drop of the filter is 64%, the regulation (regulation) by the regulator circuit, the provision of this DC electrical energy source is to provide a unidirectional variable voltage ( DC) which aims to provide practical tools in Batanghari University electric laboratories while the benefits obtained from the research results are as a tool for practical activities in the electrical engineering laboratory of Batanghari University, Jambi.